1975
DOI: 10.1017/s0043174500062834
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of Barnyardgrass, Green Foxtail, and Yellow Foxtail Seeds in Soil

Abstract: Seeds of barnyardgrass [Echinochloa crus-galli (L.) Beauv.], green foxtail [Setaria viridis (L.) Beauv.], and yellow foxtail [Setaria lutescens (Weigel) Hubb.] were buried 2.5, 10, and 20 cm deep in irrigated and nonirrigated sandy loam. Samples were exhumed periodically for 15 yr to determine viability. Viability declined with time. Three percent or less of the seeds of each species remained viable 13 yr after burial, and none were viable after 15 yr. Survival of seeds under apparently uniform conditions vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 2 publications
1
60
0
Order By: Relevance
“…1983 for Sorghum halepense. Seed dormancy and survival is consistent up to 18-21 months but from then onwards, replicates of shallow buried and surface seed were very variable, which has been previously pointed oul by other authors (Egley& Chandler, 1978;Dawson & Bruns, 1975).…”
Section: Discussionmentioning
confidence: 51%
“…1983 for Sorghum halepense. Seed dormancy and survival is consistent up to 18-21 months but from then onwards, replicates of shallow buried and surface seed were very variable, which has been previously pointed oul by other authors (Egley& Chandler, 1978;Dawson & Bruns, 1975).…”
Section: Discussionmentioning
confidence: 51%
“…4 to the studies in Table 2B would be valid. Comparison of estimates of a for the Dawson and Bruns (1975) data with and without this approximation showed that the error it introduces can be large. However, since fitting persistence data in place of survival data should underesti-'E 100 mate a, the approximation can provide additional information on the lower limit of a in real systems.…”
Section: Curve Depth Referencementioning
confidence: 75%
“…A few studies (Stoller and Wax 1973, Proud-Williams et al 1983a, Moss 1985 provided coordinated information ori emergence and survival that was used to compute the response of seed survival to depth (Tables 2A and 3). In addition, the persistence data of Dawson and Bruns (1975) were adjusted to estimate seed survival by assuming that the total emergence reported all occurred during the 1st yr. Parameters were estimated by fitting Eq. 4 to data using nonlinear least squares regression without weighting.…”
Section: Curve Depth Referencementioning
confidence: 99%
“…We simulated dynamics of a weed species noted for seedbank persistence (Abutilon theophrasti Medicus, Lueschen and Andersen, 1980) and of a more transientseedbank species (Setaria viridis [L.] Beauv., Dawson and Bruns, 1975). Model parameter values for simulations were developed using data and observations from an ongoing study (Mortensen, 1990) of an experimental 4-yr crop rotation (oat/clover-corn-soybean-corn) established at Mead, Nebraska.…”
Section: Methodsmentioning
confidence: 99%